Morphologies of Phenytoin Crystals at Silica Model Surfaces: Vapor Annealing versus Drop Casting - Ehmann, Heike M. A. (American Chemical Society, 2014)
[Image: see text] The controlled preparation of different crystal morphologies with varying preferential orientation with respect to the substrate is of crucial importance in many fields of applications. In this work, the controlled preparation of different phenytoin morphologies and the dependency of the preferential orientation of those crystallites is related with the preparation method (solvent annealing vs drop casting), as well as the physical–chemical interaction with the solvents in use. While solvent annealing induces the formation of particular structures that are partially dewetted, the drop casting technique from various solvent results in the formation of needle-like and elongated structures, with each having a distinct morphology. The morphologies are explained via the Hansen solubility parameters and correlated with the solvent vapor pressures. X-ray diffraction experiments reveal preferential orientations with respect to the solid substrate and indicate the surface-mediated stabilization of an unknown polymorph of phenytoin with an elongated unit cell in the b-axis.